Produtividade de cenoura em função de doses de nitrogênio e épocas de plantio - Oliveira, Daniela Marques de (Universidade Federal Rural do Semi-Árido, 2015)
Carrot is one of the largest economic expression of vegetables in the world, and plays an important role in feeding, especially in providing vitamin A in the diet of children and adults. For market, it is an ideal vegetable, as it ensures the supply throughout the year and has relative conservation under refrigeration. The aim of this study was to evaluate the productivity of nitrogen fertilization on carrot function in two seasons. The experiments were conducted in Horta Teaching, Department of Plant Sciences at the Federal Rural University of the Semi-Arid in Mossoró, RN, in two periods: from August to December 2013 (SEASON 1) and from June to October 2014 (SEASON 2 ). The experimental design was a randomized block with seven treatments and five replications. The treatments consisted of seven nitrogen rates: 0 (control); 20; 40; 60; 80; 100 and 120 kg ha-1 of N. The following characteristics were evaluated: percentage of long roots, medium and short, business productivity, non-commercial yield and total yield, plant height, dry matter of roots and shoots and the content N in the diagnostic sheet. The greater commercial yield was 25.26 t ha-1, with 81 kg ha-1 of N. The experiment conducted in the period from June to October 2014 provided the highest amount of long roots. The N fertilization rate in the literature for the carrot provided better performance. Planting in autumn-winter season provided larger yield, with highest percentage of long fruit
Carrot yield in different nitrogen dose and planting dates
Keywords: Carrot; Vegetable - business productivity; Nitrogen fertilization; Cenoura; Hortaliça - produtividade comercial; Adubação nitrogenada; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO